2017
DOI: 10.18203/2320-1770.ijrcog20174691
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and sociodemographic correlates of vaginal discharge among married women of reproductive age group at a teaching hospital

Abstract: Background: Vaginal discharge is the commonest reproductive tract infection among rural women in many community based studies in India. Recent evidence shows that the association between vaginal discharge and reproductive tract infection is weak. Psychosocial factors also contribute to vaginal discharge. So, the problem of vaginal discharge can be best understood not only in the biomedical perspective but also in the socio-cultural perspective. Proper understanding of this problem helps in initiating appropria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
12
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 12 publications
3
12
1
Order By: Relevance
“…In the present study, the prevalence of vaginal discharge was higher in women who were employed than those who were housewives and this difference was found to be highly statistically significant. This finding is similar to that reported by Guntoory et al 18 The most probable reason could be high degree of stress among working women.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…In the present study, the prevalence of vaginal discharge was higher in women who were employed than those who were housewives and this difference was found to be highly statistically significant. This finding is similar to that reported by Guntoory et al 18 The most probable reason could be high degree of stress among working women.…”
Section: Resultssupporting
confidence: 92%
“…This can be due to depression and psychosocial stress which is described as the medically unexplained component of white discharge. 19 This finding is similar to the finding reported by Guntoory et al 18 In the present study, the correlation between education and the prevalence of vaginal discharge was found not to be statistically significant, which is dissimilar to the findings reported by Guntoory et al, Patel et al and Chaudhary et al who reported a decrease in the prevalence of vaginal discharge with increasing educational status of the woman. 18,20,21 Vaginal discharge was found to be more prevalent in women belonging to lower class than middle and high class women and the difference was found to be statistically significant.…”
Section: Resultssupporting
confidence: 73%
See 3 more Smart Citations